Do heart rate variability indices present potential to predict late postmenopausal? A retrospective study - de Carvalho, Tatiana Dias; Norberto, Alex Rey; Oliveira, Fernando Rocha; da Silva Paiva, Laercio; Baracat, Edmund Chada; Júnior, José Maria Soares; Vanderlei, Luiz Carlos Marques [UNESP]; Sorpreso, Isabel Cristina Esposito (FapUNIFESP (SciELO), 2022)
OBJECTIVES: This study aimed to compare heart rate variability indices in early and late postmenopausal women and assess their correlation and prognostic value to predict late postmenopausal. METHODS: An observational and retrospective study was performed with the medical records of patients from Hospital das Clínicas, Faculdade de Medicina da Universidade de Sao Paulo between 2018 and 2019. We selected medical records of women with menopause, over 40 years old, which were divided into two groups, according to postmenopausal time, i.e., early and late postmenopausal. RESULTS: We analyzed data from 123 women (55 in the early and 68 in the late postmenopausal group). RRtri (triangular index) was lower in the late postmenopausal group (8.68 vs. 7.15, p=0.040). There was a significant weak negative correlation in SDNN, RRtri, and SD2 and postmenopausal time. RRtri presented the potential to predict late postmenopausal. CONCLUSION: The increase in postmenopausal time decreases global heart rate variability indices. The geometric index RRtri was significantly lower in late postmenopausal women and presented the potential to predict late postmenopausal.
Keywords: Autonomic nervous system; Climacteric; Gynecology; Heart rate determination; Postmenopause; ROC curve